Medusa-head Antibodies-More than Cerebellar Ataxia: Report of Two Cases. (5th December 2022) - Liu, Lei; Zhang, Jingxiao
Abstract : Objective: To report an anti-metabotropic glutamate receptor 1 (mGluR1) encephalitis case present with cerebellar ataxia and a paraneoplastic retinopathy and optic neuropathy case with anti-inositol 1, 4, 5-trisphosphate receptor type 1 (ITPR1) antibodies. Background: Medusa-head antibodies refer to a group of autoantibodies with a staining pattern resembling a Gorgon's head, caused by binding of IgG to Purkinje cell somata and dendrites in tissue-based assay. Although these antibodies often related with cerebellar ataxia, increasing cases presented or accompanied with encephalopathy or peripheral neuropathy have been reported. Design/Methods: Cases report. Results: Case 1: A 48-year-old woman presented with acute dizziness and unsteady gait developed head titubation, repeated language and calculation impairment. Her neural antibodies were negative with commercial kits. Further investigation showed serum and CSF "Medusa head" staining pattern of Purkinje cell in rat cerebellum. An in-house cell-based assay proved the existence of anti-mGluR1 antibodies. One-year follow-up revealed serum antibodies titers dramatically decreased and CSF antibodies negative after using steroids and intravenous immunoglobulin, but still left prominent cerebellum atrophy and severe cerebellar deficits. Case 2: Two years ago, a 61-year-old man presented with painless nasal defects of right eye, photopsia and progressed to 1 m/FC within 3 days. A similar episode happened 7 months ago in his left eye. Prior malignancy including renal carcinoma and lung adenocarcinoma discovered seven and four months ago, respectively. On admission, visual acuities were OD 50 cm/FC and OS 1 m/FC. There was a right RAPD. MRI showed bilateral optic nerves atrophy. Serum AQP4, MOG and paraneoplastic antibodies were all negative. ITPR1 antibodies were proved by tissue-based assay and Euroimmun cell-based assay. He didn't accept immunotherapies and was discharged. Conclusions: Besides cerebellar ataxia, anti-mGluR1 antibodies may also cause encephalopathy symptoms. Our findings indicate a possible role of autoimmunity to ITPR1 in the pathogenesis of paraneoplastic retinopathy and optic neuropathy and expand the panel of diagnostic markers for this condition.